(untitled) - Bestor, Theodore C. (Stanford, Calif., 1989)
Neighborhood Tokyo is one of only a handful of books in English that offers a realistic and insightful portrait of the lives of ordinary people in this vibrant global metropolis. It provides an intimate and well-grounded account of the daily life of a particular neighborhood located near the heart of the city. Yet, in addressing issues that apply to numerous other downtown neighborhoods, it gives us a sense of the organization and dynamics of daily life throughout much of central Tokyo.
Keywords: Neighborhood; Japan